Tug of War over Financial Assistance: Which Way Forward for Eurozone Stability Mechanisms? - Rehm, Moritz (2021)
This article analyses the development of financial assistance in the Eurozone since 2010. It argues that reforms to instruments and bodies, notably the European Financial Stability Facility, the European Stability Mechanism, and the current Covid-19 recovery fund, are best explained by a re-occurring pattern of negotiations between potential creditors and debtors based on common Eurozone interests and national cost-benefit considerations. Building on a liberal intergovernmentalist approach, this article shows how this pattern influenced the step-by-step reform of financial assistance in the Eurozone. The threat to Eurozone stability served as a constant factor encouraging member states to expand and deepen the assistance formula. Creditors’ cost-benefit considerations were key for retaining disincentives, a limited liability for common debt, and intermediary borrowing and lending within the financing design. However, on the back of common Eurozone interests, debtors were able to push for an increase in assistance, an expansion of assistance into areas of banking sector support, and a softening of moral hazard elements in the more recent Covid-19 pandemic. Due to creditors’ continuous insistence on safeguards and limited burden-sharing, reform outcomes were repeatedly unable to resolve the difficulties at hand.